2000
DOI: 10.1007/s004280000237
|View full text |Cite
|
Sign up to set email alerts
|

Age changes of neuromuscular junctions in the extensor digitorum longus muscle of spontaneous thymoma BUF/Mna rats

Abstract: BUF/Mna rats spontaneously develop thymomas and cause muscle weakness of hind legs at an advanced age. This rat strain has been recognized as a suitable animal model for human myasthenia gravis or related myopathies. To characterize the structural changes of neuromuscular junctions (NMJs) in BUF/Mna rats, subneural apparatuses (SNAs) of extensor digitorum longus muscles of young-adult (4-month-old) and aged (22- to 25-month-old) male rats were examined using scanning and transmission electron microscopy. The S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…8). 38 Our studies of MG with MuSK antibodies showed that the structure of NMJ is not statically maintained; rather, the nerve‐to muscle and muscle‐to‐nerve signals stimulate dynamic assembly and disassembly of NMJ's molecular complexes. A steady flow of molecular complexes at NMJ sustains both the structures and functions of the motor system, including motoneurons and muscles.…”
Section: Aging and Nmjmentioning
confidence: 85%
“…8). 38 Our studies of MG with MuSK antibodies showed that the structure of NMJ is not statically maintained; rather, the nerve‐to muscle and muscle‐to‐nerve signals stimulate dynamic assembly and disassembly of NMJ's molecular complexes. A steady flow of molecular complexes at NMJ sustains both the structures and functions of the motor system, including motoneurons and muscles.…”
Section: Aging and Nmjmentioning
confidence: 85%
“…Indeed, thymomas have been described in a variety of animals, both mammals and birds. Among mammals, thymomas develop almost consistently in inbred BUF/Mna rats [92][93][94], but rarely in other rat strains and wild rats [95], except for Praomys (Mastomys) natalensis that shows thymomas in up to 30%…”
Section: Potential Animal Models For Tamg Thymomas In Animalsmentioning
confidence: 99%
“…Anatomical studies in laboratory animals have shown that, in aged muscles, some presynaptic nerves exhibit terminal sprouts, and that postsynaptic AChR clusters are often fragmented into lots of small islands instead of a typical pretzel-like structure; however, these structures are rarely observed at NMJs in young adult muscles [6][7][8][9][10] . In addition, electron microscopic study has shown that labyrinthine synaptic gutters observed at young adult NMJs become simplified into a number of cup-like depressions at aged NMJs 11) . On the presynaptic side, it has been shown that the number of active zones and the expression level of Bassoon, a scaffold protein essential for assembly of the active zone, was significantly reduced at the nerve terminals of NMJs in aged mice 12,13) .…”
Section: Age-associated Changes Of the Nmjmentioning
confidence: 99%